Endogenous Business Cycles and Systematic Stabilization Policy - Marta Aloi; Teresa Lloyd-Braga; Hans Jørgen Whitta-Jacobsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
We study the effects of stylized fiscal policy rules on the (global) determinacy of rational expectations equilibrium in perfectly competitive monetary model with constant returns to scale and labor as the unique input. Government spending on transfers and/or demand implies a distortion of the mnetary steady state due to the implied income or inflationary taxation. We show that policy rules for which the GNP share of government spending depends sufficiently negatively on increases in GNP can stabilize the economy with respect to endogenous fluctuations for an arbitrarily small level of distortion of the steady state at which stabilization occurs. These policy rules do not involve features such as positive lump sum taxation, negative income taxation, or exact knowledge of the economy's laissez faire steady state.
Keywords: 330; Monetäre Wachstumstheorie; Konjunkturtheorie; Finanzpolitik; Regelbindung; Globalsteuerung; Rationale Erwartung; Theorie